Simplifying and Enhancing Access to Full-Text Articles with LibKey Discovery. - London, Jessie; McArthur, Barbara; Vardeman, Kimberly; Henry, Cynthia L. (Information Technology & Libraries, 2025)
Content delivery mechanisms in web-scale discovery services can often fall short of patron expectations. The Texas Tech University Libraries integrated Third Iron's LibKey Discovery with Ex Libris Primo in response to patron feedback that accessing full-text articles from Primo required too many clicks. Following implementation, researchers conducted user testing to assess the usability and usefulness of the integration. They also analyzed LibKey Discovery and link resolver usage data across the year following the launch to evaluate its impact on how patrons accessed full-text articles. Patrons responded positively overall to LibKey Discovery, perceiving it as more efficient and quicker to use. Statistics showed an increase in LibKey link usage and a corresponding decrease in link resolver clickthroughs. This article provides an overview of the implementation process, describes assessment methodologies and findings, and discusses implications for improving usability and increasing usage.